APPLICATION OF THE PERMENDAGRI NO. 64 2013 ON LISTING OF TAX ACCOUNTING HOTELS : (Study on Regional Revenue Board of Blitar Regency) - Dian Nurul Dwitayanti (JOSAR (Journal of Students Academic Research), 2018)
Since the enactment of Law No.22 of 1999 concerning Regional Government, the regional government has been given the right, authority and obligation to regulate and manage regional government affairs. The Regional Revenue Agency (BAPENDA) of Blitar Regency is one of the regional government agencies that has the responsibility to record revenues from the local tax sector and report it to the public as a form of transparency. Hotel tax is one type of local tax collected by the local government of Blitar Regency, this is in accordance with PERDA No.2 Year 2017. The purpose of this study is to find out the implementation of the Minister of Home Affairs No.64 of 2013 on hotel tax accounting records in BAPENDA Blitar Regency. The type of research used in the study is a qualitative method with data analysis techniques in the form of qualitative descriptive analysis and data triangulation. The results of the study show that BAPENDA in recording has used the accrual basis effectively at the beginning of 2017. However, in the recording of hotel tax receipts there are still records of accounting journals that have not been carried out by the treasurer of BAPENDA Blitar Regency